MANAJEMEN BADAN USAHA MILIK DESA DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI DESA COGREG KECAMATAN PARUNG - Alamsari, Daffa Ramadhan; Atthahara, Atthahara; Febriantin, Kariena (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
Management of Village Owned Enterprises (BUM Desa) in Increasing Village Original Income (PADes) in Cogreg Village, Parung District, Bogor Regency. This study explains how the management of village-owned enterprises (BUM Desa) is carried out in Cogreg Village. Collecting data using interview techniques, observation, and documentation. The research method used in this study is a qualitative approach with a descriptive type. The data sources used in this study consisted of primary and secondary data, which were strengthened by the results of interviews with informants, including the village-owned enterprise director, village-owned enterprise treasurer, village-owned enterprise supervisor, and village-owned enterprise secretary. The results of the research as a whole, Management of Village Owned Enterprises (BUM Desa) in Cogreg Village, are seen by four indicators, namely, planning, organizing, implementing, and supervising, which are still not optimal. This can be seen in the organization that has not found competent people, the implementation, which is still constrained due to coordination that has not gone well, and the provision of information that has not been maximized to the public. Keywords: Management, Village Government, Village Owned Enterprises